Penerapan Green Accounting pada Wisata Pantai Kurenai dalam Upaya Mengatasi Permasalahan Lingkungan - Hasan Abdullah Kilo; Sahmin Noholo; Muzdalifah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to find out how Green Accouting is implemented in Kurenai Beach Tourism. This research uses a qualitative method with a case study approach with data collection carried out using the interview method. The informants in this research are the Kurenai Beach Tourism Manager and Kurenai Beach Tourism Visitors. The results of this research indicate that Kurenai Beach Tourism has not implemented Green Accounting. This is because Kurenai beach tourism has not made a special report regarding environmental costs. Apart from that, environmental costs are not fully in accordance with Hansen and Mowen's theoretical framework. The implementation of Green Accounting in Kurenai Beach Tourism is still not effective due to obstacles such as lack of education and the absence of obligations in implementing it. However, Kurenai Beach Tourism always tries to maintain the sustainability and cleanliness of the surrounding environment.